KECERDASAN ANAK DALAM PERSPEKTIF ALQURAN - Tamrin, Tamrin (Rausyan Fikr: Jurnal Ilmu Studi Ushuluddin dan Filsafat, 2019)
Understanding children’s intelligence is a very important thing for the bright future of children. The responsibility of children’s intelligence is on all parties directly or indirectly related to their lives, Parents on a small family scale to a country or the world in a wider scope. Children’s intelligence consists of Intelligence Quotient, emotional Quotient and spiritual Quotient. On this matter, this article will analyze the Qur’anic view in emphasizing the position of each intelligence through several terms such as lafadz al-qaql, al-lub, al-bashar, al-fikr, al-tadabbur and al-zikr. The Qur’an provides the foundation that children’s intelligence is a fundamental thing and humans have been given a number of instrument to improve that intelligence.